Perubahan Pengetahuan dan Sikap Terhadap Pencegahan Miopia Melalui Permainan Roda Putar - Hanifatul Ulya; Sidiq, Rapitos; Hayati, Neni Fitra; Amos, John; Silaban, Evi Maria Lestari (Puslitbang Sinergis Asa Professional, 2023)
SD Al-Azhar 32 Padang is one of the schools with a high level of competition and is a full-day system school with students all day at school. Students' low knowledge and attitude toward myopia prevention are the causes of myopia in school-age children. Myopia prevention efforts need to be made to reduce the incidence of myopia in schoolchildren. This activity can be supported by a rotating wheel educational game tool. This study aims to determine changes in the knowledge and attitudes of schoolchildren toward myopia prevention efforts at Al-Azhar 32 elementary school in Padang. This research uses mixed-methods research (quantitative-qualitative), qualitatively using exploratory case studies and quantitatively using a quasi-experiment with a one-group pretest and posttest design. The population in this study were fifth-grade elementary school students, with a sample size of 64 people. Sampling technique with a purposive sample Informants in the study were eye health workers, health promotion workers, elementary school teachers, and graphic design experts. Data analysis consisted of univariate analysis and bivariate analysis with a paired t-test. The design of the rotating wheel educational game tool is attractive, and the colors vary. The average knowledge obtained before and after the intervention was 7.13 and 11.45, while the average attitude before and after the intervention was 37.23 and 44.06. The results showed that there was an average change in knowledge (p-value = 0.0001) and attitude (p-value = 0.0001). The conclusion of this study is that there are changes in the knowledge and attitudes of elementary school children toward myopia prevention efforts at Al-Azhar 32 elementary school in Padang. It is hoped that the school will follow up by incorporating education on myopia prevention efforts with a rotating wheel educational game into UKS activities at school.